Juridical Analysis of The Decision of The Maros State Court of The Legal Sure of The Right to The Land - A Muhajir; A Muin Fahmal; Sufirman Rahman (Gerechtiheid Law Journal, 2020)
This study aims: 1). To review the basis for the consideration of the panel of judges in deciding the case Number: 17Pdt.G/2015.PN.MRS. 2). To study the legal consequences of the Maros District Court Decision Number: 17 Pdt.G/2015.PN.MRS. This research uses normative legal research methods, using primary and secondary legal materials. The collection of legal materials is carried out by reviewing the relevant regulations and laws and then processing it with a qualitative analysis analysis. The results showed that: 1) Legal Basis for Consideration of the Judge of the Maros District Court Number: 17 Pdt.G/2015.MRS Implementation of Actions The Head of the Maros Regency National Land Agency Office in issuing Freehold Certificate Number 00007/Desa Abbulosibatang on behalf of Rukaya has acted is not accurate and has contradicts the general principles of good governance, especially the principles of legal accuracy and certainty. 2) The legal consequence of the decision of the Panel of Judges Number: 17 Pdt.G/2015 The suitability of MRS of the Minister of Agrarian Affairs 11 of 2016 concerning the Settlement of Land Cases on the verdict is to cancel the certificate of land rights, which states that they do not have legal power over the certificate of land rights the. So it is necessary to process land registration for the first time again at the local National Land Agency Office by submitting an application letter and the necessary attachments.